Optimización del método de perforación y voladura mediante la caracterización mecánica del macizo rocoso del bloque 330 de la compañía MINESADCO S.A, cantón Portovelo provincia de el Oro. - Elizalde Mora, Telmo Reineiro (2015)
The "OPTIMIZATION METHOD OF DRILLING AND BLASTING THROUGH THE MECHANICAL CHARACTERISTICS OF ROCK MASS 330 BLOCK COMPANY Minesadco SA, CANTON Portovelo province of gold", has been developed through the use of qualitative assessment methods and quantitative type. The study area is located in the county of the province Portovelo Gold in the neighborhood called El Paraiso. In pattern recognition blasting currently undertaken by the company Minesadco SA, he described how the activities are performed in the drilling and blasting, when starting the project taking into account the parameters of passport used by the company and the different aspects negative on the drilling and blasting method. He also proceeded to define how the processes of drilling techniques are driven into the existing rock mass in the study area. Another fundamental aspect that makes mechanical characterization was solid for both the host rock to the bulk of the grain. 12 sites for characterization of the massif were identified, and therefore proceed to the optimization of blasting passport and establish a viable drilling system for the type of rock mass will likely be generated by the project. This information was evaluated from a technical point of view and with the commitment by the mining company and comply strictly with the provisions of the optimization of drilling method, the drilling system project is viable. Once evaluated the drilling method they proceeded to set the parameters and correction of previous passport, which seeks to reduce the specific spending explosive substance and the number of holes for blasting.